Analisis Sistem Antrian untuk Optimalisasi Pelayanan Nasabah pada Customer Service di BNI KCP UNM - Nasir, Nasir (Institut Nalanda, 2024)
Optimal customer service is one of the main indicators of the success of banking services, especially in the customer service department. However, inefficient queues are often an obstacle in meeting customer expectations. This study aims to understand the queue system implemented at BNI KCP UNM, identify the main obstacles, and explore strategies that can improve efficiency and service satisfaction. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with customer service staff and customers, direct observation of the queue system, and analysis of documents related to service policies. The results of the study show that the current queue system faces several challenges, such as lack of flexibility in handling customer surges during peak hours, limited human resources, and lack of use of supporting technology. In addition, customer experiences reveal a sense of dissatisfaction caused by long wait times and lack of information related to the queue process. The conclusion of this study is that the optimization of the queue system requires a holistic approach, including the development of technology-based systems, improving staff competencies, and more effective communication with customers. These strategies can support the achievement of more efficient services and increase customer satisfaction at BNI KCP UNM.